Evaluating a children's television show as a vehicle for learning about historical artefacts: the value of multimodal discourse analysis. Issue 6 (2nd November 2022) - Zhang, Kunkun; Djonov, Emilia; Torr, Jane
ABSTRACT: Television, like other media, can work as a platform for promoting learning. This article illustrates the value of multimodal discourse analysis for evaluating the potential of a children's television show as a vehicle for fostering knowledge and skills in a specific subject area. Drawing on social semiotic principles and systemic functional genre theory, we examine the use of language and other modes in Teacup Travels – a show designed to introduce young viewers to historical artefacts. The analysis demonstrates that both story structure and particular semiotic resources contribute to how these objects are represented, and thus shape the TV programme's potential to engage children in learning about the past. Our findings suggest that multimodal storytelling strategies used in Teacup Travels encourage some aspects of children's historical consciousness and thinking, while backgrounding others.